Korelasi kadar glukosa saliva dengan kadar glukosa darah terhadap terjadinya kandidiasis oral pada penderita diabetes melitus (Correlation of salivary glucose level and blood glucose level with oral candidiasis in diabetes mellitus patient ) - Sumintarti Sumintarti; Fildzah Rahman (Journal of Dentomaxillofacial Science, 2015)
Diabetes mellitus (DM)is a disorder of carbohydrate metabolism which characterized by increased blood glucose level,which also increase the salivary glucose level. Glucose is a good medium for the growth of microorganisms includingC.albicans. One of the most common infections of the oral mucosa of patientswith DM is candidiasis. Chronic candidiasismay develop to be a malignancy. This study aimed to determine the correlation of salivary glucose levels with bloodglucose levels to the occurrence of oral candidiasis in patients with DM. Analytic observational study was carried outthrough the determination of blood glucose levels just by way of strip using a glucometer and salivary glucose levels with"GODPAP test enzymatic kolometrik". Oral candidiasis was determined in presenting C.albicans on 30 patients with DMwith seeding Saboround agar and gram staining. The results showed r = 0.228, which is higher salivary glucose levelsfollowed by high levels of blood glucose, and microscopic examination of Candida spores found in the whole sample,as well as Candida hyphae on two samples of the study. It was concluded that there is a correlation between salivary glucose levels and blood glucose levels, and glucose levels affect the occurrence of oral candidiasis in patients with DM.